Evaluation of Xanthophylls Extracted from Tagetes erectus (Marigold Flower) and Capsicum Sp. (Red Pepper Paprika) as a Pigment for Egg-yolks Compare with Synthetic Pigments - Santos-Bocanegra, E.; Ospina-Osorio, X.; Oviedo-Rondon, E.O. (International Journal of Poultry Science, 2004)
Three experiments were accomplished to compare the efficacy of yellow and red xanthophylls extracted from Tagetes erectus and Capsicum sp., with synthetic citranaxanthin, canthaxanthin, and ester of beta-apo-8-carotenoic pigments at different concentrations to enhance the yellow color of chicken egg yolk. In each trial brown laying hens were placed in cages, and after seven days of feeding a sorghum-soybean diet without pigments treatments were assigned. Yolk eggs were classified with the Roche yolk color fan (RYCF) or Minolta® refractometer. In the first experiment, 168 hens were randomly distributed to seven treatments with one control group, synthetic pigments, and natural xanthophylls. In the second and third experiments, 100 hens were assigned to four different treatments consisting in the same basal diet with addition of natural xanthophylls, and three combinations of apo-ester and citranaxantin. In all experiments, after four weeks of feeding these experimental diets, the color of 10 egg yolks per treatment was evaluated 10 different times every other day or twice a week. Results indicated that live performance was not affected by treatments, but the egg yolk color changed significantly according to the pigment added. Hens fed with diets with 7.5 ppm of yellow xanthophylls extracted from Tagetes and 4.0 ppm of red xanthophylls from Capsicum had yolk eggs classified as color 11.7 ± 0.1. Capsicum extract levels had linear effect over RYCF. Synthetic carotenoids gave a yolk color that varies from 13 to 14 in the highest concentration, and from 12 (5%) to 14 (43%) at the lowest concentration.